2021
DOI: 10.1261/rna.078727.121
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding proteins regulate aldosterone homeostasis in human steroidogenic cells

Abstract: Angiotensin II (AngII) stimulates adrenocortical cells to produce aldosterone, a master regulator of blood pressure. Despite extensive characterization of the transcriptional and enzymatic control of adrenocortical steroidogenesis, there are still major gaps in the precise regulation of AII-induced gene expression kinetics. Specifically, we do not know the regulatory contribution of RNA-binding proteins (RBPs) and RNA decay, which can control the timing of stimulus-induced gene expression. To investigate this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…MSI2 is critical for the development and maintenance of embryonic stem cells, hematopoietic stem cells, and neural stem and progenitor cells ( Fox et al 2015 ). It is also important for fertility in steroid-producing mouse gonadal tissue, which is consistent with our previous findings that MSI2 promotes aldosterone production in human adrenocortical cells ( Sutherland et al 2014 , 2015 ; Fu et al 2021 ). MSI2 is a prognostic marker associated with clinical outcomes in several types of cancer including myeloid leukemia, breast cancer, and ovarian cancer among others ( Ito et al 2010 ; Kharas et al 2010 ; Li et al 2015 ; Lee et al 2016 ; Kang et al 2017 ).…”
Section: Introductionsupporting
confidence: 92%
“…MSI2 is critical for the development and maintenance of embryonic stem cells, hematopoietic stem cells, and neural stem and progenitor cells ( Fox et al 2015 ). It is also important for fertility in steroid-producing mouse gonadal tissue, which is consistent with our previous findings that MSI2 promotes aldosterone production in human adrenocortical cells ( Sutherland et al 2014 , 2015 ; Fu et al 2021 ). MSI2 is a prognostic marker associated with clinical outcomes in several types of cancer including myeloid leukemia, breast cancer, and ovarian cancer among others ( Ito et al 2010 ; Kharas et al 2010 ; Li et al 2015 ; Lee et al 2016 ; Kang et al 2017 ).…”
Section: Introductionsupporting
confidence: 92%
“…Angiotensin II (AngII) stimulation of immortalized adrenocortical H295R cells is a robust model for human steroidogenesis 23,24 . We previously found that siRNA depletion of MSI2 in AngII-stimulated H295R cells led to decreased aldosterone production 22 , indicating that MSI2 promotes steroidogenesis. Therefore, we hypothesized that Ro-mediated inhibition of MSI2 would also reduce aldosterone production.…”
Section: Resultsmentioning
confidence: 92%
“…MSI2 is important for fertility in steroid producing mouse gonadal tissue, as well as, steroidogenesis in human adrenocortical cells [20][21][22] . Here we show that Ro is a potent inhibitor of human adrenocortical steroidogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…To understand how this immortalized cell line compared to normal adrenocortical cells, we asked how well the changes induced by steroidogenic stimuli were recapitulated in primary cells. We previously performed an RNA-seq time course of H295R cells stimulated with AngII and we established 12 groups of genes exhibiting distinct temporal response profiles [25]. Likewise, we stimulated H295R cells using forskolin, an activator of adenylyl cyclase, which resulted in five temporal response profiles.…”
Section: Similarity In Expression Changes and Temporal Response Between Primary Adrenocortical Cells And H295r Cellsmentioning
confidence: 99%
“…However, steroidogenesis involves interdependent molecular pathways that rely on multiple levels of gene regulation. Previous studies in H295R have delineated the temporal coordination of gene expression in response to AngII crucial for eliciting the appropriate production of aldosterone [25]. Unfortunately, gene expression dynamics in primary cells stimulated with either ACTH or AngII is limited to a handful of genes.…”
Section: Introductionmentioning
confidence: 99%